Ensuring safety in hands-on control through stability analysis of the human-robot interaction. (June 2019) - Bascetta, Luca; Ferretti, Gianni
Highlights: an admittance filter design methodology for hands-on control ensuring interaction stability. a nonlinear but simplified model of the human arm impedance. absolute stability theory to enforce a constraint on filter damping. stability is guaranteed without causing an excessive human effort. Abstract: This paper introduces a newly conceived methodology to design an admittance filter for hands-on control tasks, ensuring stability of human-robot interaction. Exploiting a nonlinear but simplified model of the human arm impedance, and a simple characterisation of the end-effector equivalent robot compliance, absolute stability theory allows to enforce a constraint on the design of the admittance filter damping. An experimental analysis, conducted on different subjects, allows to validate the human arm impedance model and determine the admittance filter parameters for linear and circular trajectories. Finally, hands-on control experiments reveal the absence of robot vibrations, induced by incipient instability, either in the robot measurements or in the feeling perceived by the human operator, and demonstrate that stability is guaranteed without causing an excessive human effort in the execution of the task.